Understanding English as a foreign language teachers' acceptance to teach online during COVID 19: a Chinese case - Yanjun, Gao; Wong, Su Luan; Md Khambari, Mas Nida; Noordin, Nooreen (Human Resource Management Academic Research Society, 2021)
To contain the spread of Covid-19, the Ministry of Education of China postponed the opening of schools for face-to-face lessons and launched an initiative of "postponement of school without suspension of learning”. Therefore, nearly all educational institutions across China moved from traditional teaching practices to online teaching in the Spring semester of 2020. English language teachers in Chinese universities had to move their traditional physical instruction to online. The paper is designed to develop a conceptual framework of English as a Foreign Language (EFL) teachers’ acceptance of online teaching during Covid-19 in Mainland China. Based on the integration of the Technology Acceptance Model (TAM) and Ely's Eight Conditions of Change (ECC) and previous research, six constructs — attitudes, subjective norm, perceived ease of use, perceived usefulness, self-efficacy, and eight facilitating conditions are selected in the proposed framework. A comprehensive understanding of the framework is expected to provide a better insight of the factors that affect EFL teachers' acceptance of online teaching during the pandemic for the stakeholders and future studies.